2023
DOI: 10.1007/s12144-023-04414-6
|View full text |Cite
|
Sign up to set email alerts
|

The parental COVID-19 anxiety and emotional exhaustion in healthcare workers: exploring the roles of resilience, prosocialness, and optimism

Abstract: Healthcare workers (HCWs) also became the main protagonist of the tragic pandemic story. They have had a markedly higher risk of becoming infected with COVID-19. Outside work, healthcare workers with children have experienced mental health challenges, including the worry that they may carry COVID-19 home and infect their children. Based on these, the current study aimed to examine the effect of parental COVID-19 anxiety on emotional exhaustion and identify the roles of resilience, prosocialness, and optimism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…The positive factors were optimism, family companionship, and connections with friends. These findings are consistent with existing research, highlighting the role of personal resources such as optimism, prosocial behavior, and resilience in effectively mitigating the adverse consequences of the pandemic on mental health (40)(41)(42). In addition, the importance of family companionship and connections with friends in alleviating mental stress has also been affirmed in other studies (43,44).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The positive factors were optimism, family companionship, and connections with friends. These findings are consistent with existing research, highlighting the role of personal resources such as optimism, prosocial behavior, and resilience in effectively mitigating the adverse consequences of the pandemic on mental health (40)(41)(42). In addition, the importance of family companionship and connections with friends in alleviating mental stress has also been affirmed in other studies (43,44).…”
Section: Discussionsupporting
confidence: 90%
“…On the one hand, the public’s attitude toward the epidemic had evolved from initial panic and anxiety to adaptation and acceptance, resulting in generally mild anxiety levels among HQHPs ( 47 ). However, multiple sporadic cases and local outbreaks, coupled with uncertainty about when the outbreak would end, contributed to a reduction in the psychological resilience of the public ( 40 ). At this stage, we explored the correlations between the influencing factors identified in the first stage and the levels of resilience and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, healthcare professionals have not been immune to chronic stress during this period [ 21 , 22 ]. Previous studies revealed that healthcare providers who were involved in direct patient care faced significant levels of fear and anxiety, compounded by concerns of potentially transmitting the virus to their family members, such as children and the elderly [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors may account for this, including the detrimental effects of isolation and quarantine protocols, diminished social support compared to pre-pandemic levels, the economic repercussions of the pandemic, and increased caregiving responsibilities [ 24 ]. This is further exacerbated by the stress associated with the potential risk of infecting and harming the individuals under their care [ 23 ]. Living with individuals who require care is linked to heightened perceived stress, primarily due to fears of illness and the potential disruption of daily activities [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have affirmed that anxiety diminishes an individual’s capacity to regulate negative emotions and increases the likelihood of experiencing emotional exhaustion (McCarthy et al, 2016; Qin et al, 2023). Studies conducted on the consequences of the COVID-19 pandemic have unveiled a significant correlation between anxiety and emotional exhaustion among healthcare professionals (Akdağ et al, 2023). Based on this, we propose that when confronted with major public health crises that pose life-threatening risks, female public employees may experience detrimental effects on their motivation to engage in public service due to the persistent anxiety and subsequent emotional exhaustion that can arise from prolonged periods of stress.…”
Section: Theoretical Foundations and Hypothesesmentioning
confidence: 99%